Adsorption of Water Vapour on the Microstructure and Stability of Cu-Zn Bimetallic Coordination Polymer - Oguntade, Bukunola K.; Watkins, Gareth M. (Tanzania Journal of Science, 2023)
A current challenge in the design of synthesis lies in the incorporation of two or more transition metals into a coordination polymer. The most widely used approach has been to incorporate a second metal as a generally innocent (coordinatively saturated) part of a linear linker as in the case of multifunctional carboxylated porphyrins (MCPs). The empirical method has been used to obtain many other types of MCPs; however, the selective, direct replacement of one transition metal within a monometallic coordination polymer via controlled stoichiometry has not generally led to maintained structural fidelity. In this present work, three pyromellitic acid complexes were synthesized at room temperature and characterized by Elemental analysis, Powder X-ray diffraction, Fourier transform infrared spectroscopy, Scanning electron microscopy, N2 adsorption-desorption Isotherm, and Thermal analysis. The reaction in water-methanol between pyromellitic acid and copper ions by ambient precipitation method formed [CuH2B4C]·5H2O. When zinc is combined with copper and the ligand, [Cu2Zn(B4C)1.5(H2O)4.5]·9H2O is formed. A repeat of this step under solvothermal condition produced Solvo-[Cu2Zn(B4C)1.5(H2O)5]·2H2O. The N2-adsorption isotherm of these compounds showed them to be Type III according to the IUPAC classification, with small pores only capable of small molecule sorption. Keywords: Coordination, microporous, polymer, pyromellitic, sorption